Employee Motivation, Job Satisfaction and Turnover Intention of the non- academic staff: The case of the University of Nottingham, U.K - Amissah, Karen (2018)
Abstract Title: Employee Motivation, Job Satisfaction and Turnover Intention of the non- academic staff: The case of the University of Nottingham, UK. Overview: Employee Motivation is an important concern in the higher education institution because of their contribution to developing quality and knowledgeable students which significantly impacts the nation. The non-academic staff play a vital and supportive role that complement the work of the teaching and research staff, without which there will not be the complete realisation of the goals of the university. For this reason, the study focus on their motivation, job satisfaction and turnover intention in the University of Nottingham, UK. Research Purpose: The study explored the relationship between motivation, job satisfaction and turn over the intention of the University of Nottingham. Methodology: A quantitative survey was conducted on a simple random sampling (N= 90) non-academic staff at the University of Nottingham, UK. Main Findings: The study found that good working relationship was the major motivating factor for the non- academic staff. Correlation analyses revealed the significant positive relationship between motivation and job satisfaction and a significant negative relationship between job satisfaction and turnover intentions. Regression analyses revealed that the nature of work was the significant job satisfaction facet that significantly and negatively predicts turnover intention of the non-academic staff at the University of Nottingham. Managerial implications: The management and human resource practitioners at the University of Nottingham need to recognise how the nature of work significantly influence the turnover intention of their non-academic staff when designing retention strategies. Contribution: These findings of the study contribute valuable new knowledge to the higher institution literature and can be useful in the retention of non-academic staff in the higher institution.